Agricultural mechanization policy in Bangladesh: An assessment of the phase III support program and recommendations for reform - Bakhtiar, M. Mehrab; Mahzab, Moogdho; Karim, Md. Aminul; Shamma, Raisa; Belton, Ben; Talukder, Md. Ruhul Amin; Kabir, Razin; Aravindakshan, Sreejith; Krupnik, Timothy J.; Ahmed, Akhter (International Food Policy Research Institute, 2025)
This report assesses Bangladesh's Phase III agricultural mechanization support program (2020–2024), examining the distribution, impacts, and governance of subsidies for agricultural machines—particularly combine harvesters (CHs). We analyze program effectiveness and identify critical imple mentation gaps using mixed-methods research combining administrative data analysis; a representative survey of 979 Machinery Service Providers (MSPs), including 400 CH MSPs sampled across 10 districts representing Bangladesh’s major agroecological zones and mechanization intensity; panel data from over 2,000 nationally representative Boro rice–producing households; and 128 qualitative interviews to analyze program effectiveness and pinpoint critical implementation gaps.